Organizational Citizenship Behavior (OCB) of Prison Officers in Social Reintegration Process (Study Case: Female Prison Class II Jakarta) - Lubis, Fatimah Malini; Rony, Zahara Tussoleha; Soegiarto, Ita (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
Indonesia has challenges in the future in guiding prisoners. With the increase in the number of prisoners resulting in overcapacity in almost all prisons in Indonesia. It is a challenge for the Directorate General of Corrections in preparing employees who are loyal and willing to work extra in fostering the overcapacity of prisons in Indonesia. The State Civil Apparatus who works as a prison officer is not a common and easy job to do. So that high OCB is needed to improve coaching services in prisons and one of the ways to reduce problems in prisons, especially in terms of integrity. This research used qualitative case study approach by snowball and purposive sampling with the informant number are 12 prison officers at Female Prison Class II Jakarta. The novelty of this research is finding out how the OCB of female employee in social reintegration process.